The anthropometric nutritional status of children 0-18 years old in the Western Cape Province of South Africa : a systematic review - Durao, Solange (Department of Public Health and Family Medicine, 2014)
This review will employ systematic methods for study selection and quality assessment, which decrease the probability of bias. The integration of data from individual studies also increases the precision of the results. Thus, the review will aim to produce valid and reliable evidence for health-care decision-making and policy planning aimed at improving the nutritional status of children in the province.